Mapping Rural Development Research in Indonesia: A Scopus Based Bibliometric Analysis (2014–2024) - Iqbal Saputra Zana; Gusti Naufal Rizky Perdana; Lara Ayu Lestari; Bulan Erika Bato; Dyah Rahayuning Perwitasari; Nayla Amalia Pangestu (Journal of Transformative Governance and Social Justice, 2026)
Rural development in Indonesia plays a crucial role in improving community welfare and reducing disparities between urban and rural areas. However, the growing body of research in this field has not been systematically mapped to understand its trends and conceptual structure. This creates a gap in identifying key themes, contributors, and the direction of future studies. This study aims to analyse research trends and identify the conceptual structure of rural development studies in Indonesia using a bibliometric approach to better understand how the field has evolved. The study employs a bibliometric analysis based on data collected from the Scopus database, covering publications from 2014 to 2024. The analysis includes co-authorship, keyword co-occurrence, and country contribution to examine research patterns, collaborations, and thematic relationships. The findings show a significant increase in publications over the past decade, with research activities dominated by major universities and national institutions. Leading authors consistently contribute to the field, indicating a concentration of research capacity. Key themes include sustainable development, community empowerment, participation, and rural welfare. Keyword mapping reveals strong interconnections between environmental, social, and governance dimensions, reflecting a shift toward integrative and multidisciplinary approaches. Rural development research in Indonesia is becoming more policy-oriented and holistic. This study provides a comprehensive overview of research trends and offers insights for developing more inclusive, participatory, and sustainable rural development policies.